Effects of Exoskeleton Gait Training on Balance, Load Distribution, and Functional Status in Stroke: A Randomized Controlled Trial - Rojek, Anna; Mika, Anna; Oleksy, Łukasz; Stolarczyk, Artur; Kielnar, Renata (Frontiers in Neurology, 2020)
Background: Recovery after stroke is a major goal of rehabilitation, but it is difficult to choose which treatment method is most beneficial for stroke survivors. Recently powered robotic exoskeletons are used in treatment to maximize the neural recovery of patients after stroke, but there are no studies evaluating the changes in balance among patients rehabilitated with an exoskeleton. Purpose: The aim of this study was to evaluate the effects of EKSO GT exoskeleton assisted gait training on balance, load distribution and functional status of patients after ischemic stroke. Methods: The outcomes are based on 44 patients aged 55 to 85 years after ischemic stroke that were previously randomly assigned into two groups: experimental (with EKSO GT rehabilitation) and control (with classical rehabilitation). At baseline and after 4 weeks of treatment the patients were evaluated on balance, load distribution and functional status using respectively a stabilometric platform, the Barthel index and the Rivermead Mobility Index. Results: In the experimental group, balance improved regarding the variables describing sway area as ellipse major and minor axis. In the control group, improvement was noted in sway velocity. After the therapy, total load distribution on feet in both groups showed a small and insignificant tendency towards reduction in the amount of uninvolved limb loading. In the control group, significant load transfer from the back- to the forefoot was noted. Both forms of rehabilitation caused significant changes in functional status. Conclusions: Both training with the use of the EKSO GT exoskeleton and classical physiotherapy lead to functional improvement of patients after ischemic stroke. However, in the experimental group, improvement was observed in a larger number of categories, which may suggest potentially greater impact of treatment with the exoskeleton on functional status. Also, both forms of rehabilitation caused significant changes in balance, but we have noted some trends indicating that treatment with exoskeleton may be more beneficial for some patients. The load transfer from the back- to the forefoot observed in control group was an unfavourable phenomenon. We suggest that the EKSO GT exoskeleton may be a promising tool in the rehabilitation of patients after stroke.